The Role of Tourism for Employment Generation in Nepal - Bhandari, Lila Raj (Nepal Journal of Multidisciplinary Research, 2019)
This study explores the contribution of tourism for employment generation that is also a major part of individual as well as national income. This is a strong pillar of the national income that may promote and upgrade the economic level of the citizens through service sectors. On the basis of secondary sources, this study has been analyzed the trend of employment generation due to tourism industry in government and private levels. Tourism industry helps not only for government level employment like: in Ministry of Tourism (MOT), Nepal Tourism Board (NTB) and Tourism Information Center (TIC) but it supports to the private sectors such as : Star Hotels, Tourist Standard Hotels (TSH), Home Stay (private and community),Tracking Agency, Travel Agency, Rafting Agency, International Airlines, Domestic Airlines, Paragliding, Tourist Transportation, and others( Porter, Guide, cook, Ultra-light) also. Descriptive research design, quantitative research method and average sampling have been applied in this research for proper analysis because of its nature. Secondary data of a decade have been selected and analyzed during this research. Under the guidance of economic growth model, development theory associates with Adam Smith, David Ricardo, Malthus, Karl Marx, and Rostow, has been applied. This study has moreover shown that the trend of employment in tourism sector has been increasing drastically during a decade which has been supported by table no 1, 2 and 3. Analyzing secondary data which was collected during the period of 2008/09 to 2017/18, this study has concluded that inadequate infrastructure, inadequate promoting activities and regularity mechanism, political unrest, lack of skilled human resources and unhealthy competition among tourism establishments were some major barriers faced by the tourism sector for employment generation. This study suggested that the government should develop tourism infrastructure including road, electricity and communication, and tourism promoting activities in government and non-government organizations. There is also an urgent need to invest more on improving hospitality skill of employees for quality tourism in Nepal.